Can antimalarial, antiviral and anti-respiratory infections Cameroonian medicinal plants be used as one of the potential ways to cure COVID-19? Pharmacological and ethnomedicinal proof - Roger, Tsobou; Yougouda, Hamawa; Guidawa, Fawa; Simplice Joël, Tatsimo Ndendoung; Marie-Louise, Avana Tientcheu; Junior Baudoin, Wouokoue Taffo; Pierre Marie, Mapongmetsem; Patrick, Van Damme (Journal of Medicinal Herbs and Ethnomedicine, 2020)
COVID-19 is a severe acute respiratory syndrome-related corona-virus SARS-CoV-2, that constitutes a pandemic threat to global public health. Unfortunately, there are no specific available therapies. This research work presents the ﬁndings of an investigation on traditional Cameroonian remedies of respiratory tract infections, malaria and viral infections, and also recipes that could serve as a baseline for the prevention, alleviate symptoms, treatment and perhaps may help for the anti-COVID-19 drugs discovery. Data on the medicinal plants were collected from traditional healers, Cameroonian medicinal plants books, the internet, and in addition to our personal experience as researchers and herbalists. Details of 85 plant species used to manage these three mentioned diseases in Cameroon and their pharmacological properties are recorded. Due to their ethnomedicinal uses and pharmacological activities, twenty-eight (28) plant species and 13 recipes are suggested for COVID-19 prevention, alleviate symptoms, treatment and baseline for anti-COVID-19 drug discovery. Amongst the proposed plants we have the following, Curcuma longa, Azadirachta indica, Zingiber officinale, Allium sativum and Ocimum gratissimum which were reported to possess certain inhibition properties against COVID-19 protease.